Beyond tariffs: The role of non-tariff barriers in dairy trade in the East African Community free trade area - Gelan, Ayele; Omore, Amos O. (Wiley, 2014)
This study used a spatial equilibrium modelling approach to quantify the relative welfare impacts of eliminating tariffs and non-tariff barriers on trade in dairy products among East African Community (EAC) member countries. The results indicated that removing tariffs only would not produce any significant welfare improvements unless it was accompanied by tradeenhancing measures such as reductions in non-tariff barriers and transport costs. In the current modelling framework, net welfare gains were higher in relatively lower-income countries like Burundi than in higher-income countries like Kenya. This indicates that reductions in trade costs may reduce regional imbalances in the EAC.